Separation of palm kernel oil from palm kernel with supercritical carbon dioxide using pressure swing technique - Sarker, Md. Zaidul Islam; Nik Ab Rahman, Nik Norulaini; Abdul Kadir, Mohd. Omar; Yoshiyuki, Sato; R. L., Smith Jr. (Elsevier Inc., 2007)
Separation of palm kernel oil (PKO) from undehulled ground palm kernel was studied for extractions performed with supercritical CO2 using initial pressurization–depressurization treatments. The pressurization-depressurization treatments are denoted as pressure swing (PS) extractions. Extractions were performed at 353.2 K and at pressures from 10 to 25 MPa. Results were compared with continuous extractions, in which supercritical CO2 was flowed through the packed bed of solids for a given time period. For the PS extractions, some intact or bound oil could be extracted from the third PS step at 15 MPa, while for continuous extractions, pressures of 20 MPa were required to obtain comparable yields. In the PS extractions, disruption of the oil glands in palm kernel granules probably lead to higher yields obtained at 20 and 25 MPa and this was confirmed with SEM micrographs. However, almost all of the oil of 47 g/ 100 g palm kernel (wet basis) could be extracted using combined PS and continuous extraction at 25 MPa. A simple correlation was developed based on the kinetic mass transfer model, which allows one to estimate the minimum amount of CO2 required for a given yield. Results are applicable to processes for separating and fractionating palm kernel oil for cocoa butter replacers.